"God is my only health insurance": a mixed-methods study on the experiences of persons with disability in accessing sexual and reproductive health services in Ghana - Abdul-Aziz Seidu; Abdul-Aziz Seidu; Bunmi S. Malau-Aduli; Bunmi S. Malau-Aduli; Kristin McBain-Rigg; Aduli E. O. Malau-Aduli; Theophilus I. Emeto; Theophilus I. Emeto (Frontiers Media S.A., 2023)
BackgroundAccess to sexual and reproductive health (SRH) services is a fundamental human right, but people with disabilities (PwDs) in low-and middle-income countries often face multiple barriers to utilisation. This study aimed to assess the level of SRH services utilisation and the enabling and inhibiting factors among PwDs in Ghana's Ashanti region.MethodsA sequential explanatory mixed-methods study design was employed, involving quantitative (n = 402) and qualitative (n = 37) data collection from PwDs. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were analysed using inductive thematic analysis.ResultsThe study found that only 33.8% of the PwDs had ever used SRH services. Utilisation was associated with sex, marital status and travel duration to health facility. The qualitative data revealed that factors at the individual, family/community and health facility levels influenced utilisation of SRH services, acting as both enablers and barriers.ConclusionPwDs had relatively low utilisation of SRH services in Ghana's Ashanti region. To increase utilisation, it is recommended to address the stigma and discrimination towards PwDs, provide more training for healthcare providers, improve the accessibility of healthcare facilities, and strengthen the national health insurance scheme. Further research could explore PwDs' SRH outcomes and strategies to improve these outcomes in Ghana.